Collocated social practices surrounding photos - Lindley, Siân; Durrant, Abigail; Kirk, David; Taylor, Alex (International Journal of Human-Computer Studies, 2009)
Without doubt, digital photographs have become the primary visual medium we use to capture, save and recollect our experiences. Consequently, the ways we interact with digital photos, archive them and share them have become cornerstone subjects in Human-Computer Interaction (HCI). In particular, a growing body of research in HCI has amassed around what can best be described as the collocated social practices surrounding photo